Propuesta didáctica para incentivar la lectura en estudiantes de quinto grado de primaria de la institución colombo florida bilingüe utilizando el cuento maravilloso como estrategia pedagógica (2017)
This degree project entitled, "Didactic Proposal to Encourage Reading in Fifth Grade Students at Colombo Florida Bilingual School by Storytelling as a pedagogical tool” seeks to encourage students’ interest towards reading and promote reading comprehension. From the observation stage, carried out during the first and second Pedagogical Practicum, in a Spanish class, it was evidenced lack of interest in reading in fifth grade students, thus a didactic unit was proposed.